Anti-inflammatory and Anti-arthritic Activity of Rosmarinic acid Isolated from Rosmarinus officinalis in an Experimental Model of Arthritis - Wei, Tianhu; Liu, Yuan; Li, Meirong (Indian Journal of Pharmaceutical Education and Research, 2021)
Background: Rosmarinus officinalis L. (family Lamiaceae is a perennial herb or small woody evergreen tree, commonly known as rosemary, which is native to the Mediterranean and Asia and reasonably hardy in cool climates. It has been used as a decoction in traditional Unani and Swedish medicine for the treatment of inflammatory diseases. Aim: To isolate rosmarinic acid (RA) from R. officinalis. leaf extract and to evaluate its protective effects against Freund’s adjuvant-induced arthritis in rats. Materials and Methods: Arthritis was induced via sub-plantar injection of 1mg heat-killed Mycobacterium tuberculosis (complete Freund’s adjuvant, CFA) into the left hind paw of rats. The experiment was designed and optimized based on published methods. Results: At 60 mg/kg, the RA fraction of the methanolic extract of R. officinalis L. exerted potentially effective anti-arthritic effects by controlling inflammation in an adjuvant-induced experimental model. Conclusion: Considering experimental findings relating to pharmacological and biochemical parameters, we conclude that oral administration of the RA fraction (30 and 60 mg/kg) from the methanolic extract of R. officinalis L. exerts anti-arthritic effects and controls inflammation in an adjuvant-induced arthritis rat model. RA is therefore a promising plant-derived anti-arthritic agent for the treatment of inflammatory disorders.
Keywords: Freund’s adjuvant-induced arthritis; Rosmarinic acid; Rosmarinus officinalis L; Histopathology; Inflammation